Juan Larrea and Eugenio F. Granell in front of "Guernica". Two interpretations from the republican exile - Rodríguez Fontela, M.ª Ángeles (Tropelías: Review of Literary Theory and Comparative Literature, 2020)
This paper presents a comparative analysis of the studies of Juan Larrea and Eugenio F. Granell on Picasso’s Guernica. Despite the personal psychological projections and divergent aesthetic transits of the two authors, the analyzed works present analogous hermeneutical keys: the common experience of the American exile —tinged with nostalgia, frustration and hope—; the militant use of the painting, perceptible in the historical-symbolic and mythical interpretation of the painting, and the apocalyptic and, however, hopeful and utopian vision. The essays carried out by those authors on the Picassian painting not only constitute critical-literary ekphrasis in the aforementioned paths, but also literary ekphrasis, verbal tables, in which the imaginative cognition of both authors is manifested with their own profiles, facing the enigmas and silences of Guernica.